Information System Development Based-on ERP and RAD Methods: Application For Activities Information Broadcasting - Sunardi Sunardi; Abdul Fadlil; Faqihuddin Al-anshori; Shoffan Saifullah (JUITA : Jurnal Informatika, 2020)
As technology develops, information systems become very important in institutions. Information systems support the delivery of information quickly and accurately. The system is a reference at the Persada Islamic Boarding School Ahmad Dahlan University to develop an information delivery system using applications integrated. Manual systems cause the information to be less relevant, requiring an integrated and comprehensive system that can effectively and efficiently deliver information to students. The application developed using Enterprise Resource Planning (ERP) and Rapid Application Development (RAD) methods. The application of these methods requires two main steps, including determining ERP and RAD for implementation. The process for obtaining an ERP method requires steps such as Material Requirement Planning, Close-Loop, and Manufacturing Resource Planning, and Enterprise Resource Planning. The RAD method requires steps such as Requirement Planning, RAD Design Workshop, and Implementation. Application testing used black-box and alpha testing. Each of these tests obtained an accuracy of 95% and 97.7%. Thus, this application can be implemented in Persada very well on mobile and desktop platforms. Besides, the app used information broadcasting to users in real-time for any information in Persada.